Double-layer waste-derived glass-ceramics prepared by low temperature sintering/sinter-crystallisation. (2nd October 2016) - Marangoni, M.; Ponsot, I.; Cicek, B.; Bernardo, E.
Abstract : Lightweight glass-ceramics with a dense surface layer were produced by a novel sintering approach. The surface porosity of a glass-ceramic body from the direct sintering of an engineered mixture of fly ash from thermal power plants, recycled soda-lime glass and boron waste (residues of the mining and purification of valuable boron containing minerals) was sealed by a glaze, deriving from the sinter-crystallisation of glass powders produced from the same mixture. The use of boron waste, providing B2 O3, allowed a substantial viscous flow, for the substrate, even at the relatively low temperature (850–950°C) adopted for a single firing treatment (simultaneous sintering of substrate and sinter-crystallisation of glaze). The dense sinter-crystallised layer, besides imparting improvements in the mechanical properties, was found to feature an enhanced chemical stability.